From V. Nabokov’s Drugie Berega (1954) to Speak, Memory (1966): Allusions to Russian Literature in the Structure of Perceptual Metaphor - Anastasiia Olegovna Drozdova; Natalia Alexandrovna Rogacheva (Известия Уральского федерального университета. Серия 2: Гуманитарные науки)
This article studies the perceptual metaphors introduced as an allusion in V. Nabokov’s autobiographies Drugie Berega (1954) and Speak, Memory (1966). The authors refer to scholarly works devoted to the peculiarities of the representation of sensual feelings in Nabokov’s works in Russian and English. For the first time, they establish that the reader’s associations are evaluated as a natural element of perception. The representation of the reader’s experience depends on the choice of language. In Drugie Berega, perceptual metaphors form reminiscent layers (Pushkin, Tolstoy, Blok) associated with the narrator’s specific childhood and youth memories. In Speak, Memory, perceptual metaphors functioning as allusions are presented explicitly: they are attributed, and they organise entire plots (for example, the plot about “Le Chemin du Pendu”). Communicating with the American reader, Nabokov highlights that the worlds of Russian classical literature are the key part of his language consciousness. The connections between language, literature, and sensorial perception are conveyed through transliterations in the English text. In comparison with the Russian autobiography, in Speak, Memory the allusive meaning of some metaphors is neutralised: the sensorial feelings are shown as a unique physiological experience. The authors prove that perceptual metaphors are used by Nabokov to comprehend the boundaries of cultural memory. Reader associations underscore the connections between different people with a common reading experience and mechanism of perception. Therefore, the perceptual metaphors functioning as allusions allow Nabokov to convey a special type of synesthesia: sensory feelings and the reader’s experience are mixed in the process of the perception.